Validation of the Portuguese Variant of the Munich Chronotype Questionnaire (MCTQPT) - Reis, Cátia; Madeira, Sara Gamboa; Lopes, Luísa V.; Paiva, Teresa; Roenneberg, Till (Frontiers in Physiology, 2020)
Introduction: Differences in how circadian clocks entrain to the 24-hour day, are expressions of different chronotypes that can range from extreme early to extreme late, from proverbial larks to owls. The Morningness Eveningness Questionnaire (MEQ) was one the firsts to assess daily preference, based on subjective self-assessment – a psychological construct. The later developed Munich Chronotype Questionnaire (MCTQ) uses instead the actual sleep timing to assess chronotype. It calculates the mid-sleep-point, halfway between onset and offset on work-free days (MSF), which is then corrected for potential oversleep on free days compensating for sleep debt accumulated over the workweek (MSFsc). MSFsc is expressed in local time and is thought to be a proxy for “phase of entrainment” of the circadian clock. The MCTQ-derived chronotype is therefore a biological construct. In the present report, we validate the Portuguese variant (MCTQPT) of the MCTQ. Portugal is of particular interest, since is thought to consist of especially late chronotypes. Methods: We have used three methods to assess the timing of daily behavior, namely the chronotype (MCTQ), the daily preference (rMEQ) and a simple self-assessment (time-of-day-type). A total of 80 healthy adults living in Portugal, with age and sex distributed according to the Portuguese population were recruited. We analyzed 4 weeks of continuous records of actimetry data to validate the MCTQPT and used the rMEQ to compare between biological chronotype (sleep timing) and psychological chronotype (daily preference). MCTQ variables were analyzed by descriptive statistics; correspondence between measurements were done by Spearman correlations or crosstabulation; in a subset of 41 individuals test-retest reliability was assessed. Results: MCTQ derived variables (MSF, MSW, MSFsc) correlated highly with their counterparts calculated from actimetry (MSW: rho=0.697; MSF: rho=0.747; MSFsc: rho=0.646; all p < 0.001). The MCTQ assessment of chronotype showed good test-retest reliability (rho = 0.905; p<0.001). rMEQ score correlates with MSFsc (rho= -0.695; p<0.001) and the agreement for the self-assessment with the MSFsc was fair (kw = 0.386; p < 0.001). Conclusions: The Portuguese variant of the MCTQ revealed to be a reliable questionnaire to assess chronotype for the Portuguese adult population, as previously reported for other countries.